Study of the antihypertensive peptide from soy protein hydrolysate produced by steam blasting treatment - Sri Peni Wijayanti; Try Surya Anditya; Noer Laily (Current Research on Bioscences and Biotechnology, 2021)
The purpose of this study was to determine the effect of steam blasting on soybeans and to evaluate the soy protein hydrolysate (SPH) resulting from steam blasting on ace inhibitory activity. Steam blasting works on the principle of heat and pressure. The research conducted begins with a process of pressure treatment and the heating time of soybeans. The pressures used were 2, 3 and 5 bar with heating time (hydrolysis) of 10, 20, 30, 40, 50 and 60 min for each pressure. Furthermore, the soybean resulting from steam blasting was analyzed for the degree of hydrolysis (DH), dissolved protein concentration, protein profile, and also its fractions. Then the ace inhibitory activity was performed on the SPH fraction. The results showed that the higher the pressure and the longer the heating time, the soybean colour from the steam blasting would turn dark brown due to the Maillard reaction. The value of % DH and protein solubility increase with a higher pressure. The % DH values ranged from 76 - 96%. The steam blasting process for soybeans also eliminates anti-nutritional properties and off-flavour compounds in soybeans and cuts protein into peptides/polypeptides. The fractionation results showed that the SPH fraction produced from the soybean steam blasting process had the highest ace inhibitory activity value of 68%, produced by the SPH fraction of 2 bar of 40 min steam blasting treatment. The SPH produced from the steam blasting process can potentially be a source of protein/peptides that can lower blood pressure (hypertension).